Strategi Lembaga Keuangan Syariah Menghadapi Pembiayaan Bermasalah Di Masa Pandemi COVID-19 - Abdul Ghofur; MA Syarifuddin; Abdul Majid Toyyibi; Retno Kurnianingsih (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2021)
The COVID-19 pandemic period is a disease outbreak that has brought the community's economy to a drastic decline because this outbreak resulted in the cessation of the community's business wheels and not only that, the banking sector, industry and so on were affected. So that people's income decreases and also results in the fulfillment of obligations, especially in payment of financing installments at Islamic financial institutions (LKS). This research is a type of descriptive qualitative research in which researchers conduct field studies to obtain accurate information by conducting interviews, from these results data analysis and data credibility are carried out in order to get good results. This results in LKS providing leeway and not everything depends on each financial institution which has its own policy, starting from reducing the amount of installment payments.